Contextual Learning Models in Improving Elementary School Critical Thinking Skills - Asri Widia Ningrum; Rahayu Condro Murti (Postgraduate, University of Mataram, 2023)
This study aims to find out how contextual learning models improve critical thinking skills in elementary schools. The method used in this study is a literature study. The data collection technique was carried out by reviewing the articles obtained with the help of the Publish Or Perish (POP) Software. The reviewed articles are used to answer the questions of this research. From the results of the research conducted, it shows that contextual learning models can improve critical thinking skills. This is because the contextual learning model applies direct involvement of students in the learning process and links it to the daily lives of students and emphasizes the ability of students to solve problems, analyze and make decisions